Hsa_circ_0088233 Alleviates Proliferation, Migration, and Invasion of Prostate Cancer by Targeting hsa-miR-185-3p - Deng, Zhi-Hai; Yu, Gan-Shen; Deng, Ke-Lei; Feng, Zhen-Hua; Huang, Qiang; Pan, Bin; Deng, Jian-Zhong (Frontiers in Cell and Developmental Biology, 2020)
Prostate cancer is the most common malignant tumor of the urinary system. The mechanisms of the initiation and progression of prostate cancer have not been fully elucidated. Increasing evidence suggests that circular RNAs (circRNAs) are involved in cancer pathogenesis. In this study, we aimed to identify differentially expressed circRNAs in prostate cancer tissues and explored the role of circRNAs in the pathogenesis of prostate cancer. By screening a circRNA microarray assay, we found that circ_0088233 was upregulated in prostate cancer tissues compared to adjacent normal tissues, and this upregulation can be verified in 46 pairs of prostate cancer and adjacent normal tissues examined using quantitative reverse transcription-PCR. The level of circ_0088233 correlated with the TNM stage. Knockdown of circ_0088233 reduced cell proliferation, migration, invasion, and induced G1 phase arrest and apoptosis. In addition, miR-185-3p was identified as the downstream target of circ_0088233 using luciferase reporter assays and a biotinylated circ_0088233 probe pull-down assay. The miR-185-3p level showed a negative correlation with the circ_0088233 level in prostate cancer tissues. Overexpression of circ_0088233 blocked the effects of miR-185-3p on cell proliferation, migration, invasion, cell cycle, and apoptosis. In conclusion, circ_0088233 may function as an oncogene and play an oncogenic role by sponging hsa-miR-185-3p. This study increases the understanding of circRNAs in the progression of prostate cancer. These results implicate circ_0088233 as a potential therapeutic target for prostate cancer.